Two new species of the genus Chitaura Bolívar, 1918 (Orthoptera: Acrididae, Oxyinae) from Sulawesi Island - Storozhenko, Sergey Yu. (Zootaxa, 2018)
Two new species, Chitaura linduensis Storozhenko, sp. nov. and C. doloduo Storozhenko, sp. nov., are described from Indonesia. Male genitalia of the type species of the genus, C. brachyptera Bolívar, 1918, are described and illustrated for the first time. The data on distribution of the Chitaura species on Sulawesi Island are clarified and showed in a map.